Evaluation of flow-induced noise, structure vibration, and flow morphology of R134a flowing through a thermostatic expansion valve - Santos Filho, Erivelto dos (2022)
The flow-induced noise in refrigerators, vending machines, and air-conditionings deserves attention since residential/commercial environments provide good acoustic propagation conditions. As additional constraints, the expansion device is usually located in the indoor unit, deteriorating the silent environment and leading to unwanted and annoying noise to the customer. Up to the present date, a limited but increasing number of studies have explored the outcome of flow-induced noise in expansion devices such as capillary tubes, short-orifice tubes, thermostatic, and electronic expansion valves. The number of studies concerning flow-induced noise in thermostatic expansion valves are even more scarce. As novelty, the current doctoral thesis aims to fill a gap in the literature by experimentally evaluating the two-phase flow morphology upstream and downstream the flow restriction, structure vibration, and external and internal flowinduced noise of R134a flowing through a commercial thermostatic expansion valve. Results were obtained for a borosilicate test section with an internal diameter of 10.12 mm for mass flow rate from 0.02 to 0.04 kg/s (mass velocity from 4583 to 36701 kg/(m2 s)), saturation pressure and temperature upstream of the expansion valve from 7.7 to 10.2 bar and from 30 to 40ºC, respectively, expanding into a low-pressure reservoir at 4.1 bar and saturation temperature of 10ºC for inlet liquid subcooled degree from -15ºC up to vapor qualities of 15% and outlet vapor qualities ranging from 8 to 34 %. This study was carried out for a commercial expansion valve with outlet orifice diameter of 2.52 mm and aperture varying from 7 to 100%. Images of the flow morphology upstream and downstream of the expansion valve were obtained and correlated with the flow-induced noise and test section structure acceleration. Isolated bubbles, coalescing bubbles, churn, and annular flow patterns were observed in the images recorded upstream the expansion valve. Downstream of the valve, the flow morphology displayed a chaotic behavior due to the fluid flashing process, therefore it was not possible to classify the flow according to well-known flow patterns as defined in the literature. In addition, the velocity of the jets exiting the expansion valve orifice was estimated along the visualization section. The flashing jet was characterized as a wave of liquid followed by dispersed bubbles. The jets exhibited an approximately constant velocity of 20 m/s for subcooled liquid upstream of the valve, regardless of the experimental condition. As the subcooled liquid evolves into two-phase flow at the valve inlet, the jet velocity increases abruptly. On the other hand, under annular flow conditions at the valve inlet, the jet velocity remains approximately constant independently of the experimental condition. In addition, the jet velocity decreases as it flows along the visualization section. Jet frequencies observed at 48 and 96 Hz were similar to the values found for the external noise. The total sound pressure level of the external noise and the structure acceleration exhibited similar trends with increasing the vapor quality at the valve inlet. Moreover, superior structure acceleration and external and internal noise were found for isolated bubbles at the valve inlet. The frequency spectrum behavior of the external noise and acceleration of the test section were almost similar, while the noise evaluated at the valve decreases asymptotically with increasing frequency. Finally, the parametric analysis revealed that the external noise and acceleration of the structure are directly related to the flow pattern, jet velocity, and vapor quality; however, a noise dependence of the mass flow and pressure drop across the expansion device was not found. Furthermore, no parametric effect of the measured and estimated variables on the internal flow-induced noise was identified. Besides, statistically it was not found effect of the inlet/outlet vapor quality, mass flow rate, external noise, test section acceleration, pressure drop, and jet velocity on the internal noise.